THE DETERMINANTS OF THE INCIDENCE OF EMPLOYER-PROVIDED TRAINING IN THE WESTERN BALKANS (The South East European Journal of Economics and Business, 2024)
If the standards of living in the Western Balkans are to converge on those in the EU then the current productivity gap needs eliminating. A significant portion of that gap would ideally be eliminated through the expansion of employer-provided training. However, survey data indicate that since 2016 training incidence has been rising in only two of the six countries of the Western Balkans. The main contribution of this paper is to investigate this disappointing performance. A model of the determinants of the incidence of employer-provided training is developed based on theory and investigations in other countries. It is found that in the Western Balkans firms with foreign owners, those who export and those who report that their employees are eager to access training are more likely to provide training, whilst micro and small firms are less likely to provide training. Sentiments regarding the firm’s and economy’s current performance and their prospects are also significant determinants. The policy implications of these findings are addressed in the concluding section.